Mapping Of Soil Corrosion of Near-Subsurface Using Resistivity Method in Banda Aceh and Its Surrounding Areas - Asrillah Asrillah; Marwan Marwan; Deassy Siska (Faculty of Engineering, Malikussaleh University, 2018)
The stiffness of foundation structures must periodically be concerned. This is very crucial to building itself. To obtain this information, the corrosion degree of near-surface soil can be investigated. This research was performed in Banda areas and its surrounding and aims to delineate the soil corrosion degree. Achieving this goal, resistivity method and pH measurement were carried out in the 14 areas consisting of Baet, Miruk Taman, Cot Iri, Lambhuk, Ulee Lheue, Punge, Deah Baro, Blang Bintang, Batoh, Lamjamee, Peukan Bada, and Lam Ateuk. For the resistivity data acquisition, the Wenner 4-pin of ASTMG57 was applied to provide soil resistivity values processed by utilizing the Res2Div software. While the pH values were probed by using the pH meter. Both data are an in-situ measurement. The processed resistivity data and pH values are combined for each area. The result shows that there are two locations predicted as the very corrosive soil which is Lamjamee and Lam Ateuk whose the resistivity and pH value of 2-6 Ωm, pH ≤ 5 and 12-20 Ωm, pH ≤ 6.31 respectively. The following types of soil are susceptible to be corrosion including Lambuk, Ulee Lheue, Punge, Batoh, Peukan Bada, and Lambaro. These potentially corrosive soils are probably influenced by moderately watered content and their pH values are normal but tend gradually to be decline by the time. The last category is non-corrosive soils existed in such areas of Miruek Taman, Deah Baro, Blang Bintang, and Lampeunerut. The whole types of soil corrosion degree are displayed on the map from which views an integral part of soil corrosive characterization.